2021
DOI: 10.3892/etm.2021.10821
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and surgical algorithm for managing iatrogenic bile duct injuries during laparoscopic cholecystectomy: A multicenter study

Abstract: The present study was a multicenter, analytical, nonrandomized research on 108 cases of intraoperative vascular and bile duct lesions during laparoscopic cholecystectomies. We selected these cases from 16,559 cholecystectomies performed entirely laparoscopically or debuted laparoscopically and converted to an open approach. The study included two surgical centers labeled as primary, with extensive experience in hepato-biliary reconstructive surgery, and four other centers labeled as secondary that referred cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
1
7
0
1
Order By: Relevance
“…The patient was referred to the hepatobiliary centre for immediate repair according to the proposed algorithm for management of BDI. 1 A photographic analysis of this classical BDI revealed that misidentification was the cause of the injury, which was consistent with the Delphi consensus. 2 Surgeons tend to interpret their visual information in terms of what they 'want' to see, and our desires can alter what we see by influencing the way we process visual information.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…The patient was referred to the hepatobiliary centre for immediate repair according to the proposed algorithm for management of BDI. 1 A photographic analysis of this classical BDI revealed that misidentification was the cause of the injury, which was consistent with the Delphi consensus. 2 Surgeons tend to interpret their visual information in terms of what they 'want' to see, and our desires can alter what we see by influencing the way we process visual information.…”
supporting
confidence: 78%
“…The surgeon observed bile leakage after dividing the two cystic structures distally and proximally. The patient was referred to the hepatobiliary centre for immediate repair according to the proposed algorithm for management of BDI 1 . A photographic analysis of this classical BDI revealed that misidentification was the cause of the injury, which was consistent with the Delphi consensus 2 .…”
Section: Figurementioning
confidence: 60%
“…The reported rate of occurrence of BDI in LC is approximately 0.5-0.85% 7 . Once bile duct injury occurs, it will bring a heavy blow to both patients and surgeons, and even seriously affect the patient's quality of life 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…The reported rate of occurrence of BDI in LC is approximately 0.5-0.85% 7 . Once bile duct injury occurs, it will bring a heavy blow to both patients and surgeons, and even seriously affect the patient's quality of life 8,9 .Anatomic variations of Calot's triangle were found to be closely associated with BDI during LC 10 . There are some important ducts in Calot's triangle, such as cystic artery, hepatic artery, accessory hepatic duct, and anatomical variations often occur here.…”
mentioning
confidence: 99%
“…Laparoscopic cholecystectomy (LC) is a common method for treating gallbladder diseases, with the advantages of small trauma, simple surgical operation, short surgical time, fast recovery after surgery, etc [1,2] . Bile duct injury (BDI) is a kind of serious and difficult surgical complications, and these complex injuries are often caused by LC, the incidence rate can reach 0.3% to 1.4% [3,4] .…”
Section: Introductionmentioning
confidence: 99%